From Leadership to Performance: Mediasi Digital Transformation di Direktorat Jenderal Perbendaharaan - Naomi Patricia Ramli; Koni Royyan; Tiara Puspa (Universitas Riau Kepulauan, 2026)
This study aims to analyze the influence of Digital Leadership and Transformational Leadership on Employee Performance mediated by Digital Transformation among employees at the Head Office and Vertical Offices within the Directorate General of Treasury, Ministry of Finance of the Republic of Indonesia. This research employs a descriptive quantitative approach with a correlational design and hypothesis testing. The population of this study consisted of all employees at the Head Office, Regional Offices (Kanwil), and State Treasury Service Offices (KPPN) within the Directorate General of Treasury, with samples selected using purposive sampling technique, yielding a minimum sample of 180 respondents based on 34 questionnaire items. The analytical tools employed include descriptive statistics using SPSS software to describe variable conditions, Structural Equation Modeling (SEM) using AMOS software to examine direct effects between variables, and the Sobel Test to assess the mediating effect of Digital Transformation. The findings indicate that Digital Leadership and Transformational Leadership positively influence Employee Performance, both directly and indirectly through the mediation of Digital Transformation, suggesting that the synergy between digital-based leadership and organizational transformation is a key driver of employee performance improvement in the era of digitalization. Keywords: Digital Leadership, Transformational Leadership, Employee Performance, Digital Transformation, Public Sector